2014
DOI: 10.1002/adma.201402782
|View full text |Cite
|
Sign up to set email alerts
|

Microcavity‐Enhanced Light‐Trapping for Highly Efficient Organic Parallel Tandem Solar Cells

Abstract: A high-performance parallel tandem solar cell employing ultra-thin Ag as the intermediate anode is demonstrated, which comprises a semitransparent front sub-cell and a microcavity assisted back sub-cell. In addition to the extended optical field as a result of the tandem architecture, the prominent microcavity resonance formed in the back sub-cell enables such a parallel tandem configuration to possess high light utilization efficiency (the peak EQE value is over 80%) and a high photovoltaic performance of 9.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 46 publications
3
86
0
Order By: Relevance
“…PCEs of 8.5% on both glass and flexible plastic substrates have been reported. 91 This corresponds to ∼20% improvement in PCE when compared to the equivalent ITO-based devices. The significantly enhanced performance was ascribed to the substantially improved photon collection by the resonant microcavity structure, which contributed to an improved photocurrent compared with devices built on ITO-coated substrates.…”
Section: Semi-transparent Organic Photovoltaic Cells With Light Trappmentioning
confidence: 99%
See 1 more Smart Citation
“…PCEs of 8.5% on both glass and flexible plastic substrates have been reported. 91 This corresponds to ∼20% improvement in PCE when compared to the equivalent ITO-based devices. The significantly enhanced performance was ascribed to the substantially improved photon collection by the resonant microcavity structure, which contributed to an improved photocurrent compared with devices built on ITO-coated substrates.…”
Section: Semi-transparent Organic Photovoltaic Cells With Light Trappmentioning
confidence: 99%
“…This approach which, until recently had been applied to opaque cells with limited success, was proven in 2014 to lead to high PCEs for opaque cells using low-band gap polymers in the absorber layer. 91 The same approach has been applied to semi-transparent devices and cells exhibiting a PCE equivalent to 90% of the PCE of the opaque counterpart have been demonstrated. 92 2 Semi-Transparent Polymer Cells…”
Section: Introductionmentioning
confidence: 99%
“…Such a tandem OPV benefited from the optimized distribution of optical field intensity through strong reflectivity generated by the ultrathin Ag layer in the front sub‐cell and the formation of a microcavity in the back sub‐cell, yielding a high PCE of ≈11% and high summed EQE over 90%. The same research group also demonstrated high performance parallel tandem OPVs comprising a semi‐transparent front cell and a microcavity assisted top‐illuminated back cell (Figure 11d) 151. Microcavity effects induced by an ultrathin intermediate Ag transparent electrode facilitated the light trapping, resulting in a record PCE of 9.2% for parallel tandem OPVs.…”
Section: Electrode Engineeringmentioning
confidence: 91%
“…In order to overcome the absorption limitation, various effective strategies have been carried out, such as the development of novel narrow bandgap photoactive materials [8][9][10], plasmonics based light trapping approaches [11][12][13] and the innovation of tandem configurations [14][15][16][17]. Recently, an elegant alternative strategy named the ternary systems containing two donors and one acceptor (or one donor and two acceptors) are attracting more and more interests due to their potentials to expand the spectral absorption range of organic semiconductors and improve the photon harvesting, thereby providing an effective route in achieving a higher short-circuit current density (J sc ) and thus a higher PCE [18].…”
Section: Introductionmentioning
confidence: 99%